Narrow-Band Excitation of Hysteretic Systems - W.Q. Zhu; C.D. Huang; T.T. Soong (Shock and Vibration)
The stationary response of smooth and bilinear hysteretic systems to narrow-band random excitations is investigated by using the quasistatic method and digital simulation. It is shown that the response is qualitatively different in different ranges of values of the ratio of the excitation central frequency to the natural frequency of the system. In the resonant zone, the response is essentially non-Gaussian. For bilinear hysteretic systems with strong yielding, stochastic jumps may occur for a range of values of the ratio between nonresonant and resonant zones.